Eco-friendly fluidized solidified loess incorporating multi-source industrial solid wastes: A systematic study from rheological features, mechanical performance, and stabilization mechanisms - Baofeng Lei; Jucong Sun; Henghui Fan; Yongxiang Cao; Changhao Liu; Haochen Zhang; Shuai Pang; Jiaze Li; Huihui Yu; Minqiang Meng (Process Safety and Environmental Protection, 2026)

A numerical study of the possible influence of the ice nucleation process on the bolt-from-the-blue lightning production - Qianwei Zhao; Zheng Shi; Yanfeng Fan; Xuedong Cui; Haochen Chen; Wenzhong Li (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

SUMOylation in Mitochondrial Quality Control: Mechanisms and Implications for Neurodegenerative Disease - Qingya Wu; Dengying Fan; Jianhui Ren; Yafang Xing; Zhengzheng Chen; Haochen Jin; Yisheng Lu; Xiaopeng Wang; Hua Zheng (Molecular Neurobiology, 2026)

Assessing the effect of a non-ionic surfactant on surface degradation of the pesticide Acetamiprid on live tea plants - Wanjun Gao; Xinyi Du; Zili Gao; Haochen Dai; Lanying Li; Bingling Zhang; Gaoxi Wang; Xuejuan Chen; Jeffery Doherty; John M. Clark; Ruyan Hou; Fan Luo; et al. (Food Research International, 2025)

Quantitative effects of potassium application on potato tuber yield, quality, and potassium uptake in China: A meta-analysis - Fan Zhang; Xiukang Wang; Hao He; Haochen Wang; Bolun Zhang; Shiju Liu; Ruixue Chen; Yaru Zhang; Yandong Wang; Hao Ren; Yu Wang; Juan Han (Field Crops Research, 2025)

Effects of warming and phosphorus on the stoichiometry of native and invasive plant and their rhizosphere soil - Miaomiao Cui; Jie Dong; Bin Yang; Haochen Yu; Xue Fan; Zhaoqi Zhu; Guangqian Ren; Daolin Du (Flora, 2025)

Intergeneric protoplast fusion for probiotic strain improvement: Molecular mechanisms and metabolic analysis - Haiting Duan; Xin Su; Qiqi Fan; Haochen Zhang; Bilige Menghe; Wenjun Liu (Food Bioscience, 2025)

In vitro induction and characterization of octaploid Schizachyrium scoparium, an ornamental grass - Zhuolin Xiao; Mingjun Wei; Yue Xu; Haochen Nie; Hui Zhang; Ke Teng; Wenjun Teng; Juying Wu; Xifeng Fan; Yuesen Yue (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A study of wave forces on a vertical truncated cylinder with different submergence depths - Yuping Fan; Jinxuan Li; Shuxue Liu; Haochen Zhang (Ocean Engineering, 2024)

Experimental and numerical analysis of wave forces on a vertical truncated cylinder with different depths of submergence under focused waves - Yuping Fan; Jinxuan Li; Shuxue Liu; Haochen Zhang (Ocean Engineering, 2024)

A comprehensive review of the environmental benefits of urban green spaces - Fan Zhang; Haochen Qian (Environmental Research, 2024)

Global Environmental Change Shifts Ecological Stoichiometry Coupling Between Plant and Soil in Early-Stage Invasions - Guangqian Ren; Miaomiao Cui; Haochen Yu; Xue Fan; Zhaoqi Zhu; Haiyan Zhang; Zhicong Dai; Jianfan Sun; Bin Yang; Daolin Du (Journal of Soil Science and Plant Nutrition, 2024)

Exploring the ecological meanings of temperature sensitivity of ecosystem respiration from different methods - Yang Zhang; Gaofeng Zhu; Kun Zhang; Heng Huang; Liyang He; Cong Xu; Huiling Chen; Yonghong Su; Yuzhong Zhang; Haochen Fan; Boyuan Wang (Science of The Total Environment, 2024)

Energy partitioning over an irrigated vineyard in arid northwest China: Variation characteristics, influence degree, and path of influencing factors - Huiling Chen; Yongtai Zhu; Gaofeng Zhu; Yang Zhang; Liyang He; Cong Xu; Kun Zhang; Jing Wang; Ramamoorthy Ayyamperumal; Haochen Fan; Boyuan Wang (Agricultural and Forest Meteorology, 2024)

Effects of distinct lipid phases and packaging on alleviating the quality deterioration of surimi gels during frozen storage - Yuxin Wang; Xidong Jiao; Nana Zhang; Bowen Yan; Haochen Ding; Weijian Ye; Jianlian Huang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Food Bioscience, 2024)

Research on the operation strategy of joint wind-photovoltaic-hydropower-pumped storage participation in electricity market based on Nash negotiation - Xudong Li; Zhongfu Tan; Junyao Shen; Jiacheng Yang; Wei Fan; Haochen Zhao; Ting Zhang (Journal of Cleaner Production, 2024)

A lightweight deep learning model for ocean eddy detection - Haochen Sun; Hongping Li; Ming Xu; Fan Yang; Qiang Zhao; Cuishu Li (Frontiers in Marine Science, 2023)
Ocean eddies are typical oceanic mesoscale phenomena that are numerous, widely distributed and have high energy. Traditional eddy detection methods are mainly based on physical mechanisms with high accuracy. However, the large number of steps and complex parameter settings limit their applicability for most users. With the rapid development of deep learning techniques, object detection models have been broadly used in the field of ocean remote sensing. This paper proposes a lightweight eddy detection model, ghost eddy detection YOLO (GED-YOLO), based on sea level anomaly data and the “You Only Look Once” (YOLO) series models. The proposed model used ECA+GhostNet as the backbone network and an atrous spatial pyramid pooling network as the feature enhancement network. The ghost eddy detection path aggregation network was proposed for feature fusion, which reduced the number of model parameters and improved the detection performance. The experimental results showed that GED-YOLO achieved better detection precision and smaller parameter size. Its mAP was 95.11% and the parameter size was 22.56 MB. In addition, the test experiment results showed that GED-YOLO had similar eddy detection performance and faster detection speed compared to the traditional physical method.

The fate of microplastic pollution in the Changjiang River estuary: A review - Yifei Li; Qingbing Lu; Jian Yang; Yi Xing; Wei Ling; Kai Liu; Qizhen Yang; Hongjie Ma; Zengxin Pei; Tianqi Wu; Haochen Guo; Ziyuan Gao; et al. (Journal of Cleaner Production, 2023)

TCDD induced lipid accumulation by impairment of autophagic flux in THP-1 macrophages - Jing Lu; Meitong Liu; Yong Fan; Haochen Zheng; Shuang Guan (Environmental Science and Pollution Research, 2021)